Komposisi Jenis dan Struktur Tegakan Berbagai Formasi Hutan di Resort Bama Taman Nasional Baluran, Jawa Timur - Istomo Istomo; Wahyu Hartarto (Jurnal Silvikultur Tropika, 2019)
Baluran National Park is a oldes national park and unique in terms of existing ecosystems. One area that is considered to be of broad condition is Bama Resort. Baluran National Park has various forest formations including mangrove formations, coastal forests, savana forests, seasonal forests, rainforests, and plain forests. This study aims to examine the composition and structure of each forest formation in Baluran National Park in East Java. The number of plant species found in mangrove forest formations were 6 species, 40 species of coastal forest, 37 species of savana forest, 44 species of rain forest, 28 species of lowland forest, and 50 species of seasonal forest formations. The highest density values were in savana forest formation at the seedlings and understorey level of 132445 ind / ha while the density at the tree level was found in the mangrove forest formation of 346 ind / ha. The diversity index of seedlings and understorey species is medium (2 <H '<3) while for other growth rates it is classified as medium and low (0 <H' <3). The value of community similarity between overall forest formations is categorized as low (values below 50%.). Overall header stratification in each formation is in strata c. Key words: Forest Formation, Species Composition, Structure, Baluran National Park